Tratamiento del infarto agudo de miocardio: avances y desafíos - Ramirez Tinoco, Brittany Del Cisne (Machala : Universidad Técnica de Machala, 2024)
Objective: To evaluate the effectiveness and feasibility of emerging strategies in the treatment of acute myocardial infarction, identifying the most promising advances and key challenges, in order to improve clinical results and comprehensive care of affected patients. Methodology: An exhaustive search was carried out in scientific databases such as PubMed, Google Scholar and Scopus, using search terms such as "acute myocardial infarction", "treatment", "emerging strategies", among others. Studies published between 2019 and 2024 that address advances in the treatment of acute myocardial infarction will be included. Development: The treatment of myocardial infarction is a continuous challenge. Among the advances, reperfusion therapy constitutes the basis of management given its association with a reduction in mortality, regardless of ST alteration. The combination of P2Y12 inhibitors and antiplatelet agents continues to be the primary indication for patients with AMI. Currently, a new pharmacological target is being investigated, Beclin1, which, based on current studies, may intervene in the process of platelet adhesion and aggregation, influencing the pathophysiology of AMI. Conclusion: Early reperfusion aims to reduce mortality; percutaneous coronary repercussion is the treatment of choice and should be performed with radial access. Antiplatelet agents are used in dual therapy in all patients with aspirin and P2Y12 inhibitors. Beclin1 influences platelet phenomena, which could indicate new strategies in its treatment.
Objetivo: Evaluar la eficacia y viabilidad de las estrategias emergentes en el tratamiento del infarto agudo de miocardio, identificando los avances más prometedores y los desafíos clave, a fin del mejoramiento en resultados clínicos y la atención integral de los pacientes afectados. Metodología: Se efectuó una búsqueda exhaustiva en bases de datos científicas como PubMed, Google Académico y Scopus, utilizando términos de búsqueda como "infarto agudo de miocardio", "tratamiento", "estrategias emergentes", entre otros. Se incluirán estudios publicados entre 2019 y 2024 que aborden avances en el tratamiento del infarto agudo de miocardio. Desarrollo: El tratamiento del infarto de miocardio es un continuo reto. Dentro de los avances, la terapia de reperfusión constituye la base del manejo dada su asociación con una reducción de la mortalidad, independientemente de la alteración del ST. La combinación de inhibidores P2Y12 y antiagregantes plaquetarios continúan siendo indicación primaria de los pacientes con IAM. Al momento se investiga un nueva diana farmacológica, el Beclin1, que en base a los estudios actuales puede intervenir en el proceso de adhesión y agregación plaquetaria, influyendo en la fisiopatología del IAM. Conclusión: La reperfusión temprana tiene como objetivo reducir la mortalidad, la repercusión coronaria percutánea es el tratamiento de elección y debe realizarse con acceso radial. Los antiagregantes plaquetarios se utilizan en terapia dual en todos los pacientes con aspirina e inhibidores de P2Y12. El Beclin1 influye en los fenómenos plaquetarios lo que podría indicar nuevas estrategias en su tratamiento.
Keywords: INFARTO AGUDO DE MIOCARDIO; TRATAMIENTO; ESTRATEGIAS EMERGENTES